Use of Electrolyzed Water as Disinfection Technology in Aquaculture Systems: Effects on Vibrio harveyi, a Significant Marine Pathogen for Marine Fish and Invertebrates - Adolfo Blasco; Pablo Ibányez-Payá; Belén Fouz; Carmen Amaro; Pedro Amorós; José V. Ros-Lis (Applied Sciences)
Background: The aquaculture sector is vital for food supply and marine species conservation. However, vibriosis poses significant threats, affecting fish and invertebrates. Vibrio harveyi outbreaks are increasing due to global warming-driven expansion of virulent strains. Methods: This study investigates the bactericidal potential of in situ-generated electrolyzed water (EW) as a complementary strategy to antibiotic therapy. Strains of V. harveyi isolated from diseased fish were exposed to EW under varying conditions of salinity (1.5 and 3%), pH (5, 6.5, and 7.5), and free available chlorine (FAC) (5, 20, 25, and 125 ppm) to reduce bacterial concentrations. Results: EW demonstrated high bactericidal potential at 20–25 ppm FAC and non-acidic pH, reducing bacterial populations by over four logarithmic units within 15 min. Efficacy diminished when EW was stored for days. Conclusions: EW shows a promising disinfection method during vibriosis outbreaks and as a preventive measure during stress in aquaculture. Its advantages include on-site production and avoidance of concentrated chemicals, which minimize health risks.